The Ferroxidase Hephaestin in Lung Cancer: Pathological Significance and Prognostic Value - Zacchi, Paola; Belmonte, Beatrice; Mangogna, Alessandro; Morello, Gaia; Scola, Letizia; Martorana, Anna; Borelli, Violetta (Frontiers in Oncology, 2021)
Hephaestin (HEPH) belongs to a group of exocytoplasmic ferroxidases which contribute to cellular iron homeostasis by favouring its export. Down-regulation of HEPH expression, possibly by stimulating cell proliferation due to an increase in iron availability, has shown to correlate with poor survival in breast cancer. The lung is particularly sensitive to iron-induced oxidative stress, given the high oxygen tension present, however, HEPH distribution in lung cancer and its influence on prognosis have not been investigated yet. In this study we explored the prognostic value of HEPH and its expression pattern in the most prevalent histotypes of lung cancers, namely lung adenocarcinoma and lung squamous cell carcinoma. In silico analyses, based on UALCAN, Gene Expression Profiling Interactive Analysis (GEPIA) and Kaplan-Meier plotter bioinformatics, revealed a significant correlation between higher levels of HEPH expression and favorable prognosis, in both cancer histotypes. Moreover, TIMER web platform showed a statistically significant association between HEPH expression and cell elements belonging to the tumor microenvironment identified as endothelial cells and a subpopulation of cancer-associated fibroblasts, further confirmed by double immunohistochemical labelling with cell type specific markers. Taken together, these data shed a light on the complex mechanisms of local iron handling lung cancer can exploit to support tumorigenesis.